Pemberdayaan Perempuan Dalam Meningkatkan Ekonomi Keluarga Melalui Diversifikasi Pelatihan Pembuatan Stik Kelor Di Desa Rabakodo Kabupaten Bima - Kusumayadi, Firmansyah; Irawan, Ikbal; Hamidah, Nur Khusnul; Muthiah, Hanifah; Safriani, Safriani (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Women play an important role in economic development and improving household welfare. However, obstacles such as fear of starting a business, lack of understanding about business opportunities, business development, lack of entrepreneurial creativity, and lack of skills in producing home industries cause many women in Rabakodo Village to not have a business. Rabakodo Village is one of the central trading villages and there is several natural potentials that can be processed and developed. Observations made on the potential of natural resources have not been able to improve people's lives due to the lack of community skills in processing local products that have selling value. The aim of the training is to explore and hone women's abilities and provide encouragement and motivation for women to be able to run businesses independently. The results of observations and analysis reveal that empowering women through training and mentoring can help women earn better incomes and strengthen their position in the family and society. It is hoped that the training that has been provided can help the community to improve the economic welfare of their families.